Employing the Stress or Accent in the Structural Approach a Rhythmic Study - Ali, Warda Ibrahim; Al-Badrani, Alaa Hussein Aliwi (Journal of Ecohumanism, 2025)
Stress constitutes an essential part and an active element of rhythm in Arabic poetry, in addition to being an important component of the rhythmic structure. However, it was employed by the structuralist approach as a critical criterion to reveal its role in forming that rhythmic structure, not merely as a part of it. Its critical functions varied, as stress contributes to influencing the rhythmic units by giving distinctiveness to the syllabic segments through the points of stress reliance within them. Moreover, it adds artistic aesthetics and symbolic indications that enrich the rhythmic structure and deepen the sense of perception for the recipient. It contributes to creating an element of attraction through its harmonious tonal waves within regular rhythmic patterns in the poetic structure.Therefore, studying stress has distinctive rhythmic characteristics in the structuralist approach, and stress has ancient roots that precede Orientalists, albeit with lesser focus and attention. Classical Arabic poetry abounds with various types of stress when studied within this approach.